Railway Safety Perspectives: Trends, Concerns and Future Directions - Atul Sarojwal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Rail transport has significantly transformed human mobility, and with its continuous development, the focus on train and infrastructure safety—particularly concerning passengers—has become increasingly critical. This paper examines the various methods adopted to ensure high levels of safety in railways through an extensive review of existing literature. A total of 48 relevant articles were shortlisted for in-depth analysis, combining bibliometric research with a comprehensive literature assessment to evaluate current safety management practices in the railway sector. In recent years, high-speed rail systems have drawn considerable attention from experts and railway authorities due to their higher risk potential. Consequently, numerous advanced technologies, supported by artificial intelligence and machine learning, are being developed worldwide to guarantee consistently high safety standards. Among the most sensitive areas are railway stations, especially platform zones, which represent critical hotspots for accidents, including suicide incidents. Various preventive strategies have demonstrated measurable improvements in safety, reinforcing railways as one of the safest modes of transport infrastructure. Building on these advancements, the application of resilient safety models could further strengthen safety performance and ensure more robust protection for passengers and operations.